ANTIDEPRESSANT DRUG ADMINISTRATION TO MICE THROUGH INTRANASAL, INTRAVENOUS AND ORAL ROUTES: FROM BIOANALYSIS TO PHARMACOKINETICS - Mestre, Catarina Guerreiro (2021)
Dissertação de Mestrado em Farmacologia Aplicada apresentada à Faculdade de Farmácia